Meta-Analyses of Human Cell-Based Cardiac Regeneration Therapies: What Can Systematic Reviews Tell Us About Cell Therapies for Ischemic Heart Disease?. Issue 8 (15th April 2016) - Martin-Rendon, Enca
Abstract : Controversies from basic science, discrepancies from clinical trials, and divergent results from meta-analyses have recently arisen in the field of cell therapies for cardiovascular repair and regeneration. Noticeably, there are almost as many systematic reviews and meta-analyses published as there are well-conducted clinical studies. But how do we disentangle the confusion they have raised? This article addresses why results obtained from systematic reviews and meta-analyses of human cell-based cardiac regeneration therapies are still valid to inform the design of future clinical trials. It also addresses how meta-analyses are not free from limitations and how important it is to assess the quality of the evidence and the quality of the systematic reviews and finally how stronger conclusions can be drawn when several pieces of evidence converge.